Octreotide for conservative management of postoperative chylothorax in the neonate - Rocha, G (2007)
Chylothorax is a possible complication after thoracotomy. Treatment is initially conservative and includes drainage and correction of nutritional losses. Surgical treatment is reserved for cases not responsive to medical measures. The authors report on the clinical case of a premature neonate with a traumatic chylothorax secondary to esophageal atresia surgical correction. The use of octreotide allowed the resolution of the effusion without adverse effects and avoided the surgical treatment.